Analisis Profil Kecelakaan Konstruksi pada Proyek Bangunan Gedung di Indonesia - Masiku, H.; Latief, R.U.; Parung, H.; Arifuddin, R. (Tadulako University, 2024)
The construction sector is the highest contributor to construction accidents, which is 31.9% of the total construction accidents. One of the leading causes of accidents is the need for more awareness from workers and companies of the importance of implementing OHS at work. This situation arises due to the need for maximum planning and implementation of the Construction Safety Management System through the Minister of Public Works and Public Housing, and the Indonesian government has issued Regulation Number 10 of 2021 concerning construction safety guidelines. Data collection in this study is secondary data, namely construction accident reports by the Construction Safety Committee. The analysis used is archival analysis, where the report is mapped to produce statistics on construction accidents based on the type of project, time of occurrence, day of occurrence, the impact of the accident, and the cause of the accident. The results showed that the building became the first rank of construction project types with a percentage of 35% where the occurrence was in the morning before noon, namely 08.00-12.00, and on Tuesday became a day that often occurred construction accidents based on the construction safety committee. It was found that the cause of the accident was dominated by human factors and work equipment, which would impact the damage to the building itself with a percentage of 56%. The results of this study will be helpful for implementers/construction accident experts as guidelines for the future